Understanding food security issues in remote Western Australian Indigenous communities - Pollard, Christina; Nyaradi, A.; Lester, M.; Sauer, K. (Australian Health Promotion Association, 2014)
Issue addressed: Food insecurity in remote Western Australian (WA) Indigenous communities. This study explored remote community store managers’ views on issues related to improving food security in order to inform health policy. Method: A census of all remote WA Indigenous community store managers was conducted in 2010. Telephone interviews sought managers’ perceptions of community food insecurity, problems with their store, and potential policy options for improving the supply, accessibility, affordability and consumption of nutritious foods. Descriptive analyses were conducted using SPSS for Windows version 17.0. Results: Managers stated that freight costs and irregular deliveries contributed to high prices and a limited range of foods. Poor store infrastructure, compromised cold chain logistics, and commonly occurring power outages affected food quality. Half of the managers said there was hunger in their community because people did not have enough money to buy food. The role of nutritionists beyond a clinical and educational role was not understood. Conclusions: Food security interventions in remote communities need to take into consideration issues such as freight costs, transport and low demand for nutritious foods. Store managers provide important local knowledge regarding the development and implementation of food security interventions. So what?: Agencies acting to address the issue of food insecurity in remote WA Indigenous communities should heed the advice of community store managers that high food prices, poor quality and limited availability are mainly due to transport inefficiencies and freight costs. Improving healthy food affordability in communities where high unemployment and low household income abound is fundamental to improving food security, yet presents a significant challenge.